Acute biliary conditions in geriatrics: analysis of 151 observations, therapeutic fundaments and results - Piacenza, Guillermo; Mesa, Guillermo; Sáez, Hugo (Cirugía del Uruguay, 1975)
Seventy. two out of the 151 patients studied were operated upan within 48 hours after adrnission. Because of the usual severity of the cases, cholecystostomy was pref.,,rred in_ 45 cases, using local anaesthesia in many of them (18). In this group mortality was high, generally because of associated affections. In patients in whom surgery was delayed so that they were better balanced, 27 cholecystectomies and only 18 cholecystostomies were performed. In 29 out of 54 cases the cornmon hile duct was acted upon. Five of the patients who had been cholecystectomized had to be re-operated r.'ue to r2sidual biliary pathology. When distal stenosis or panlithiasis were present, choledocoduodenostomy was preferre:i, obtaining excellent results. The incidence of fistulas and evisceration was higher than in younger adults. General mortality in the series was 12.6 % .